Evaluation of energy consumption in small scale distillation pot based on integral control signal for real time implementation / Nurul Nadia Mohammad … [et al.] - Mohammad, Nurul Nadia; Marzaki, Hezri; Azman, Ahmad Aftas; Adnan, Ramli; Tajuddin, Saiful Nizam; Rahiman, Mohd Hezri Fazalul (Faculty of Electrical Engineering, Universiti Teknologi MARA, Shah Alam, 2017)
This paper presents the comparative performances of PID controller with several tuning rules that includes Ziegler-Nichols, Cohen-Coon and Integral Square Error (ISE)-Load that was based on real time implementation. The characteristic of water temperature of hydro distillation process have been modelled by obtaining First Order Plus Dead Time (FOPDT). In this study, a setpoint was set up to 80°C to evaluate those tuning rules in term of transient responses such as settling time, rise time and percentage of overshoot. Moreover, another performance criteria in term of energy consumption have been evaluated by using integral control signal. The result shows that PID controller with Cohen Coon tuning gives the best performances for transient analyses and also gives lower energy consumption compared to other tuning rules